Productivity Tracking: A Survey of Critical Care Pharmacist Practices and Satisfaction. (April 2022) - Forehand, Christy Cecil; Fitton, Kathryn; Keats, Kelli; Chase, Aaron; Smith, Susan E.; Sikora Newsome, Andrea
Introduction: The position paper on critical care pharmacy services describes two tiers of responsibilities: essential and desirable activities. Activities are categorized into five domains: patient care, quality improvement, research and scholarship, training and education, and professional development. Documentation of these activities can be important for justifying pharmacist positions, comparing pharmacy practice models, conducting performance evaluations, and tracking individual workload; however, limited recommendations are provided for standardized productivity tracking, and national practices remain largely uncharacterized.Objectives: The purpose of this survey was to describe documentation practices of critical care pharmacist activities.Methods: A cross-sectional survey was distributed via email to 1694 members of the ACCP critical care practice research network. The survey asked respondents to describe the methods used to document productivity as it relates to the 5 domains.Results: Seventy-nine (4.7%) critical care pharmacists from 63 institutions completed the survey. Intervention documentation was used for position justification and annual reviews among 54.4% and 44.1% of pharmacists, respectively. Pharmacists were routinely expected to perform additional responsibilities beyond patient care that contribute to overall productivity, but the percentage of institutions that track these activities as a measure of pharmacist productivity was relatively low: quality improvement (46%), research/scholarship (29%), training/education (38%), and professional development (27%). Documentation of these additional responsibilities and activities was primarily used for annual evaluations, but the majority of respondents answered that no standardized method for tracking activities existed. In multivariate regression, dedicated ICU pharmacists was a significant predictor for increased satisfaction (Exp(ß) 4.498, 95% CI 1.054-19.187, P = .042).Conclusion: Practice variation exists in how and for what intent critical care pharmacists track productivity. Further evaluation and standardization of productivity tracking may aid in position justification and practice model evaluation for dedicated ICU pharmacists in today's value-based era.